Presidents and Cabinets: Coordinating Executive Leadership in Premier-Presidential Regimes. (February 2020) - Raunio, Tapio; Sedelius, Thomas
A key factor of semi-presidential regimes is power-sharing mechanisms between president and government. Influenced by Shugart and Carey's seminal work on premier-presidential regimes, this article addresses intra-executive dynamics in light of recent scholarship on the risks and consequences associated with conflict and cooperation between the president and the cabinet. Through an in-depth comparison of three premier-presidential systems with broadly similar constitutional designs, Finland, Lithuania and Romania, it forces us to reconsider how coordination mechanisms and political context shape presidential influence. Absent of a working constitutional division of labour and established modes of intra-executive coordination, presidents are more likely to use alternative channels of influence – such as the strategy of 'going public' or direct contacts with political parties, the legislature or civil society stakeholders – and to intervene in questions falling under the competence of the government. Lack of institutionalized coordination also benefits the presidents as they hold the initiative regarding cooperation between the two executives.